Ciri – ciri sistem ekonomi islam : dalam prespektif al-qur’an dan hadits - Farhan, Muhammad Fariza; Barokah, Rakan; Adiib, Muhammad Faiq; Furqon, Fauzan Arif (Maliki Interdisciplinary Journal, 2026)
This article examines the key characteristics of the Islamic economic system based on the Qur’an and Hadith as normative foundations that regulate human economic behavior. Islamic economics emerges as an alternative to capitalism and socialism, which often fail to ensure justice and social balance. Core principles such as monotheism (tawhid), justice (‘adl), balance (tawazun), prohibition of usury (riba), fair distribution of wealth, and social responsibility serve as essential elements in constructing a humane and sustainable economic order. The Qur’an emphasizes equitable wealth distribution, prohibition of exploitation, and integrity in transactions, while the Hadith provides practical guidance such as prohibiting hoarding, fraud, and encouraging honesty in trade. This study demonstrates that Islamic economics is not only normative but also highly relevant to addressing modern economic challenges characterized by inequality and moral crises. By integrating spiritual, social, and material dimensions, Islamic economics offers a holistic solution for human welfare.